The Relationship Between Vocabulary and Reading Comprehension of Senior High School Students - Kandisa, Juliana; Nazri, M. Adib; Agustina, Yulia; Prasetyaningrum, Ari (Journal of English Language and Education, 2025)
Although many studies have explored the relationship between vocabulary mastery and reading comprehension, research in vocational school contexts is limited, where students face unique challenges in learning English. This study aimed to examine the correlation between vocabulary mastery and reading comprehension among eleventh-grade students of SMK NW Pancor in the 2024/2025 academic year. A quantitative correlational design was used, involving 22 students selected through purposive sampling. Vocabulary mastery was measured using a 20-item multiple-choice test covering synonyms, antonyms, definitions, and sentence completions, while reading comprehension was assessed with a 20-item multiple-choice test focusing on main ideas, specific information, inference, and vocabulary in context. Data were analyzed using descriptive statistics, normality tests, and the Pearson Product Moment correlation. The results revealed a strong and significant positive correlation between vocabulary mastery and reading comprehension (r = 0.753, p 0.001), indicating that students with higher vocabulary knowledge tended to achieve better reading comprehension. These findings highlight the essential role of vocabulary development in supporting reading skills and suggest that integrating systematic vocabulary instruction into English lessons can improve students’ overall language proficiency in vocational school settings.